The ‘Civil Death’ of Persons Deprived of Legal Capacity in the Republic of North Macedonia - Ignovska Elena (Iustinianus Primus Faculty of Law, 2024)
The author tackles the topic on legal capacity in the intersection between civil law and human rights that is very important, yet neglected in the Macedonian legal theory and jurisprudence. Namely, Republic of North Macedonia has ratified the Convention on Rights of Persons with Disabilities and has an obligations to align its legal system (primarily its Family Law and Law on Non-contentious Procedure, but also other laws) with its spirit. It seems like the concept of legal capacity does not include variations of the mental capacity in the Court’s decision. Instead, it is binary in terms that the legal capacity can be either limited/deprived or not, without further specification of the scope of rights and obligations encompassed therein. As a result, persons deprived from legal capacity (and sometimes persons with limited legal capacity) are limited to enjoy and act upon most of their fundamental rights. The author concludes that persons deprived from legal capacity in the Macedonian legal system are in ‘civil death’ because they are restricted from enjoying and acting upon many fundamental human rights. These include equality rights (not to be discriminated against), private and family life rights (right to make decisions about their own body, medical treatments, reproductive choices, conclusion of marriage, recognition of parenthood etc), procedural rights (right to access to court and administrative institutions, right to express legally valid opinions in such proceedings), political rights (right to vote) etc. This should be changed as a matter of priority in the future.
Keywords: legal capacity, deprivation, restoration, civil law, human rights